The THE USE OF WEB-BASED EXAM (WBE) TO OPTIMIZE STUDENTS TESTING RESULT - Abdul Ngafif (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2017)
Some basic problems found during the test occurred in mid and final test using the conventional testing system are the students tend to do cheating, the sleepy supervisors, the inconsistency of test time, and the risk of losing the answer sheet. To overcome those problems, the researcher applies a concept called web-based exam system which uses three main tools to run the system. First, it uses teacher’s laptop as the server; second, the teacher makes the questions using the software (web-based exam software) in his own laptop; third, it uses access point to communicate the server and the user (students’ laptop). From the result of the research, it can be seen that this system can overcome the problems found in conventional testing system and it needed no paper.